Quantification of ADF STEM images of molybdenum chalcogenide nanowires - Cosgriff, E; Nicolosi, V; Coleman, J; Nellist, P (2006)
Molybdenum chalcogenide nanowires have potential applications in some of the same areas as carbon nanotubes but are, as yet, not as well understood structurally. Previous investigations to determine atomic structure using x-ray diffraction and high-resolution transmission electron microscopy have been inconclusive. Images obtained using an annular dark field detector in an aberration corrected scanning transmission electron microscope have provided an additional means of structure determination. Simulations of the electron scattering within the sample were performed by including thermal diffuse scattering into a multislice routine. Such simulations allow insight into the location of certain atomic species and the nature of the packing into bundles of the wires. It is also shown that for structure refinement, a simple object function approach is sufficient, rather than a full dynamical calculation.